SAFETY OF RAPID RITUXIMAB INFUSION POST 72 HOURS OF ADMINISTRATION - Dora SP Lang; Chng Wee Joo, (The Malaysian Journal of Nursing (MJN), 2013)
Rapid rituximab infusion, IgGl monoclonal antibody targeting CD20, at 90-minute is used widely in the treatment ofB-cell lymphoproliferative disorders. The aim of the study was to evaluate the safety of application ofrapid rituximab at 90-minutes among non-Hodgkin lymphoma. This is a prospective clinical trial using a convenient sampling. Prior to the rapid infusion, the patients received different combinations of pre-medication as per physician's choice. In this case, the patients received 20% of the total volume of rituximab over 30 minutes and the remaining 60% over 60 minutes. The adverse event was monitored using NCI CTCAE version 4 during infusion until 72 hours post infusion. A total of 12 patients participated in the study and received 25 cycles of rapid rituximab infusion. Only one patient experienced grade 2 vomiting at 48 hours post infusion. Thus it was concluded that the rapid rituximab infusion was safe and feasible for non-Hodgkin Lymphoma patient seeking treatment in our institution.